2023
DOI: 10.3389/fmed.2023.1195568
|View full text |Cite
|
Sign up to set email alerts
|

Morphologic variants of Meibomian glands: age-wise distribution and differences between upper and lower eyelids

Saumya Srivastav,
Mohammed Hasnat Ali,
Sayan Basu
et al.

Abstract: PurposeTo evaluate the distribution of various Meibomian gland morphologies across different age groups in healthy individuals.MethodsThe infrared meibographic morphologies of the Meibomian glands from the upper and lower eyelids of 236 healthy individuals (472 eyes; mean age 38.4 ± 17.5 years; 80 female participants: 156 male participants) were evaluated for their prevalence and differences across six decades of life, from 10 to 80 years. A linear mixed-effects modeling test was performed for statistical anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 20 publications
0
2
0
1
Order By: Relevance
“…Common symptoms of MGL include dryness, foreign-body sensation, itchy eyes, and blurred vision. Previous studies have found a strong correlation between the MGL area and the Ocular Surface Disease Index questionnaire score, proposing that MGL of more than 32% can be considered a dry eye-related symptom [19][20] . This study found that the incidence of increased ocular secretion significantly differed among the four area loss groups and that the incidence of ocular secretion significantly increased as the area loss degree increased.…”
Section: Meibomian Gland Area Lossmentioning
confidence: 98%
“…Common symptoms of MGL include dryness, foreign-body sensation, itchy eyes, and blurred vision. Previous studies have found a strong correlation between the MGL area and the Ocular Surface Disease Index questionnaire score, proposing that MGL of more than 32% can be considered a dry eye-related symptom [19][20] . This study found that the incidence of increased ocular secretion significantly differed among the four area loss groups and that the incidence of ocular secretion significantly increased as the area loss degree increased.…”
Section: Meibomian Gland Area Lossmentioning
confidence: 98%
“…3). Варианты морфологических изменений мейбомиевых желез, определяемые с помощью мейбографии[40] Different meibomian gland morphologies detected on meibography[40] Примечание. Белыми стрелками показаны соответствующие изменения.…”
unclassified
“…There are approximately 30 to 40 glands located in the upper eyelid with a length of approximately 5.5 mm and 20 to 30 glands in the lower eyelid with a length of approximately 2 mm to 4 mm. Significant gland shortening has been observed in individuals aged 30 years and above, 8 , 9 and gland shortening has also been associated with dry eye disease. 10 , 11 These glands are formed by multiple acini, comprised of meibocytes which terminally differentiate to produce meibum.…”
mentioning
confidence: 99%